Implementation of supply chain integration and influence on operational performance in bakery factory in Poasia district, Kendari city - Hadinda Hadinda (Institute of Accounting Research and Novation (IARN), 2024)
One of the company's problems is that the supply chain is poorly integrated, impacting operational performance. This study aims to see the implementation of supply chain integration and its impact on operational performance. The research methods are qualitative and quantitative. The population of this study was a bakery in the Poasia subdistrict, Kendari City. The sample of this study was 44 employees working in a bakery in the Poasia subdistrict, Kendari City. The sampling uses a census approach, which takes the entire population as a sample. Research Results The study results show that supplier integration has a positive effect on operational performance, customer integration has a positive impact on operational performance, and internal integration has a positive effect on operational performance. This study concludes that supply chain integration positively impacts operational performance.